2020
DOI: 10.1016/j.vas.2020.100100
|View full text |Cite|
|
Sign up to set email alerts
|

Dental pathology of the wild Iberian wolf (Canis lupus signatus): The study of a 20th century Portuguese museum collection

Abstract: Highlights Dental pathology of wild Iberian wolf was studied in 61 complete skulls and 4 mandibles from a museum collection. Museum collections can provide crucial information about wild elusive species. The most frequent observed abnormalities were tooth wear, periodontitis and tooth fractures. Dental radiography is of a great importance for the diagnose and classification of the dental and periodontal conditions. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In the wild, Algerian psammodromus [Psammodromus algirus (Linnaeus)] lizards showed a cline of variable telomere length across a latitudinal gradient of their habitat (Burraco et al, 2020). In terms of age-related telomere studies, telomere length has been shown to decline with age in American alligators (Scott et al, 2006;Bae et al, 2021), as well as loggerhead sea turtles (Hatase et al, 2008;Plot et al, 2012). Conversely, telomeres were found to increase in length in tropical water python [Liasis fuscus (Peters)] ( Ujvari & Madsen, 2009) and follow a curvilinear relationship in frilled lizards [Chlamydosaurus kingii (Gray)] with both increases and decreases across their full lifespan (Ujvari et al, 2017).…”
Section: Speciesmentioning
confidence: 99%
“…In the wild, Algerian psammodromus [Psammodromus algirus (Linnaeus)] lizards showed a cline of variable telomere length across a latitudinal gradient of their habitat (Burraco et al, 2020). In terms of age-related telomere studies, telomere length has been shown to decline with age in American alligators (Scott et al, 2006;Bae et al, 2021), as well as loggerhead sea turtles (Hatase et al, 2008;Plot et al, 2012). Conversely, telomeres were found to increase in length in tropical water python [Liasis fuscus (Peters)] ( Ujvari & Madsen, 2009) and follow a curvilinear relationship in frilled lizards [Chlamydosaurus kingii (Gray)] with both increases and decreases across their full lifespan (Ujvari et al, 2017).…”
Section: Speciesmentioning
confidence: 99%
“…Pathologies of the teeth and periodontium of wild carnivores have been studied intensively [4,5]. Comprehensive investigations focusing on dental pathologies among members of the Canidae family have been conducted extensively in various European nations.…”
Section: Introductionmentioning
confidence: 99%